2019
DOI: 10.1089/crispr.2019.0006
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR-Cas9 Causes Chromosomal Instability and Rearrangements in Cancer Cell Lines, Detectable by Cytogenetic Methods

Abstract: CRISPR-Cas9 has quickly become the method of choice for genome editing, with multiple publications describing technical advances and novel applications. It has been widely adopted as a tool for basic research and has significant translational and clinical potential. However, its usage has outpaced the establishment of essential and rigorous controls for unwanted off-target effects, manifested as small mutations, large deletions of target loci, or large-scale chromosomal rearrangements. A common application of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
55
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 20 publications
(22 reference statements)
0
55
0
Order By: Relevance
“…These effects were also noted in conjunction with templated editing in mice (33)(34)(35)(36). Extensive loss-of-heterozygosity by gene conversion and megabase-long deletions were also observed (37)(38)(39)(40). Such outcomes could be pathogenic, and may be hard to genotype.…”
Section: Introductionmentioning
confidence: 88%
“…These effects were also noted in conjunction with templated editing in mice (33)(34)(35)(36). Extensive loss-of-heterozygosity by gene conversion and megabase-long deletions were also observed (37)(38)(39)(40). Such outcomes could be pathogenic, and may be hard to genotype.…”
Section: Introductionmentioning
confidence: 88%
“…Two studies 5 , 6 previously reported incidental chromosome arm truncation following CRISPR/Cas9 targeting telomere-proximal genes: POLE 5 located 11 kb and UROS 6 located 6 million bp away from chromosome arm end. ZNF516 is located 6 million bp from the telomere, whereas MEX3C , targeting which did not induce arm truncation, is located 31 million bp away from the arm end.…”
mentioning
confidence: 99%
“…Reports by Rayner et al. 5 and Cullot et al. 6 suggested detection of arm truncation with FISH analysis for targeted genes; however, this can only be achieved after cell colony expansion and involves several experimental steps.…”
mentioning
confidence: 99%
“…For the remaining 4 clones, the damage apparently completely prevented amplification of the second allele. This highlights the importance of in-depth genotyping following CRISPR-Cas9-mediated mutagenesis, as previously noted (Kosicki et al, 2018, Cullot et al, 2019, Rayner et al, 2019, Przewrocka et al, 2020. We therefore sought to test whether clones #18 and #19, compound mutants with two frameshifted alleles predicted to introduce premature stop codons in the sequence encoding the third zinc fingers (FIG.S7D-F), were null for KLF17 expression.…”
Section: Klf17 -/-Hescs Are Not Impaired In Their Ability To Adopt Namentioning
confidence: 91%